Cholesterol depletion suppresses thermal necrosis resistance by alleviating an increase in membrane fluidity - Taisei Kanamori; Shogo Yasuda; Runjing Duan; Mei Ohashi; Mai Amou; Kanato Hori; Ryota Tsuda; Taiki Fujimoto; Kenjirou Higashi; Wei Xu; Takuro Niidome; Hiroto Hatakeyama (Scientific Reports)
Abstract Thermally resistant cancer cells suppress the therapeutic effects of hyperthermia. However, the mechanism underlying the thermal resistance remains unclear. With the aim of enhancing the therapeutic effects of hyperthermia, we investigated the mechanism underlying thermal resistance. We found that heat shock-induced cell death can be classified into two types: late-phase apoptosis and early-phase necrosis. Cell death was suppressed in thermally resistant cells. In addition, heat-induced necrosis resistance correlated with plasma membrane fluidity, which was maintained by cholesterol. Depletion of cholesterol from cancer cells and tumor tissues enhanced the effect of hyperthermia under both in vivo and in vitro conditions. Hence, the findings demonstrate the usefulness of cholesterol as a marker for thermally resistant cancer cells. Furthermore, the combination of cholesterol depletion and hyperthermia may be a new therapeutic strategy for thermally resistant cancers.